Climate change and frequency-intensity-duration (FID) curves for Florya station, Istanbul - Guclu, Y. S.; Sisman, E.; Yelegen, M. O. (WILEY, 2018)
In recent decades, according to Intergovernmental Panel on Climate Change reports, the impact of climate change on hydro-meteorological events has increased substantially. This point is obvious in many rainfall-runoff time series as a negative or positive trend. In this paper, first of all such trend possibilities are searched graphically according to Sen's 1:1 (45 degrees) straight-line method, which has been proposed instead of the classical methods including Mann-Kendall, Spearman's rho and linear regression approaches. Additionally, these trends are quantified by using frequency-intensity-duration (FID) curves, instead of intensity-duration-frequency (IDF) curves obtained from a set of single storm rainfall records. The FID curves provide practical, easy and clear representation of rainfall intensity variation through fitted exponential curves with coefficient of determination that is almost equal to 1 (R-2 approximate to 1). FID curves are drawn on semilogarithmic paper with rainfall intensity estimations from the convenient Gamma probability distribution functions (PDFs) or cumulative distribution functions (CDFs). In this study 46-year rainfall records are used from Florya station, which is located in Istanbul, Turkey. The comparisons generally indicated that a negative trend is valid at this station, and accordingly, representative FID curves are obtained on ordinary and semilogarithmic papers for this station.
Keywords: Climate change; cumulative distribution function (CDF); frequency-intensity-duration (FID) curves; intensity-duration-frequency (IDF) curves; probability distribution function (PDF); semilogarithmic paper; trend; TREND ANALYSIS; Environmental Sciences & Ecology; Water Resources